Altitude, geological substrate, and dynamics of Natura 2000 habitat types in Cretan low-vegetation pastures - Frederic Bendali; Michel Godron (Academia Environmental Sciences and Sustainability)
New Greek legislation imposes conservation goals for habitat types (HTs) in sites of (European) community interest (SCI), so the ecological equilibrium status must be checked before impact assessment in these sites. We processed 1,875 vegetation samples (relevés) from the previous Conservation Status Assessment campaign in Crete (2014–2015) concerning low-vegetation pastures in 29 SCI. We conducted a frequency analysis to find vegetation groups (VGs) and relevés groups (RGs) using the same matrix species × relevés. We present a general table where the RG are defined by their habitat code and class values of altitudinal and geological substrates. We also used ecological profiles on these variables to fine-tune the differences within the VG. These methods led to phytosociological and ecological precisions: in the grass habitats (HT code 6220), the class of Lygeo sparti–Stipetea tenacissimae is on tertiary substrate at an altitude below 210 m, the Helianthemetea guttati is below 1,250 m on hard limestone and at a low altitude on noncalcareous substrate, while the Stipo–Trachynietea distachyae is below 800 m and is not substrate-restricted. Concerning phryganas and heaths, the altitude at 1,500 m separates HT 5420-5430 downward, associated with classes Ononido–Rosmarinetea and Cisto–Lavanduletea stoechadis, from HT 4090 upward, associated with the Daphno–Festucetea. The altitude of HT 5420 remains downward of 800 m. HT 4090 and 5430 are also characterized by calcareous geological substrates, namely hard limestone and marble. We suggest that HT 5420 is the most post-cultural vegetation and HT 5430 is a long-term pasture on noncultivable substrates.